Operation Mode on Pulse Modulation in Atmospheric Radio Frequency Glow Discharges - 张杰 郭颖 黄晓江 张菁 石建军 (Plasma science & technology, 2016)
The discharge operation regime of pulse modulated atmospheric radio frequency （RF） glow discharge in helium is investigated on the duty cycle and frequency of modulation pulses. The characteristics of radio frequency discharge burst in terms of breakdown voltage, alpha（s）- gamma（γ） mode transition voltage and current are demonstrated by the discharge current voltage characteristics. The minimum breakdown voltage of RF discharge burst was obtained at the duty cycle of 20% and frequency of 400 kHz, respectively. The α-γ mode transition of RF discharge burst occurs at higher voltage and current by reducing the duty cycle and elevating the modulation frequency before the RF discharge burst evolving into the ignition phase, in which the RF discharge burst can operate stably in the γ mode. It proposes that the intensity and stability of RF discharge burst can be improved by manipulating the duty cycle and modulation frequency in pulse modulated atmospheric RF glow discharge.